Multiscale models of neural tissue - Catan, Funda (2016)
The brain is a complex system which contains a large number of neurons. This complex nature of the brain can be simplified by mathematical models. Mathematical models are almost equally as important as biological experiments and represent some part of the real world by mathematical terms. They help us to understand mathematical neuroscience. The functional dynamics of brain and the behaviour of neurons have become popular recently. Hence, mathematical neuroscience becomes an attractive prospective to study because of a large availability of biological and computation data.